Table of Content - - (Journal of engineering sciences and information technology, 2024)
Table of Content: 1. Applying an ecosystem for the Development of Scientists, Sciences, and Sovereign Knowledge to a National case Dr. AbdulHamid AbdulRahman Al-Abduljabbar , Dr. Bandar Abdullah Al-Saud 2. Principles of Cloud Computing Infrastructure IaaS Housam Ghanim Alhazeem 3. Exploring the Versatility of Aluminum in Mechanical Engineering Eng. Mohamed Ahmed Alawady 4. Enhancing Cross-Age Facial Recognition with T2T-ViT Networks and Multi-Scale Attention Decomposition Zakarya Mutahar Al-Haeer, Li Mengxia